Under-reported aspects of diagnosis and treatment addressed in the Dutch-Flemish guideline for comprehensive diagnostics in disorders/differences of sex development. Issue 9 (17th April 2020) - Bever, Yolande van; Brüggenwirth, Hennie T; Wolffenbuttel, Katja P; Dessens, Arianne B; Groenenberg, Irene A L; Knapen, Maarten F C M; De Baere, Elfride; Cools, Martine; van Ravenswaaij-Arts, Conny M A; Sikkema-Raddatz, Birgit; Claahsen-van der Grinten, Hedi; Kempers, Marlies; et al.
Abstract : We present key points from the updated Dutch-Flemish guideline on comprehensive diagnostics in disorders/differences of sex development (DSD) that have not been widely addressed in the current (inter)national literature. These points are of interest to physicians working in DSD (expert) centres and to professionals who come across persons with a DSD but have no (or limited) experience in this area. The Dutch-Flemish guideline is based on internationally accepted principles. Recent initiatives striving for uniform high-quality care across Europe, and beyond, such as the completed COST action 1303 and the European Reference Network for rare endocrine conditions (EndoERN), have generated several excellent papers covering nearly all aspects of DSD. The Dutch-Flemish guideline follows these international consensus papers and covers a number of other topics relevant to daily practice. For instance, although next-generation sequencing (NGS)-based molecular diagnostics are becoming the gold standard for genetic evaluation, it can be difficult to prove variant causality or relate the genotype to the clinical presentation. Network formation and centralisation are essential to promote functional studies that assess the effects of genetic variants and to the correct histological assessment of gonadal material from DSD patients, as well as allowing for maximisation of expertise and possible cost reductions. The Dutch-Flemish guidelines uniquely address three aspects of DSD. First, we propose an algorithm for counselling and diagnostic evaluation when a DSD is suspected prenatally, a clinical situation that is becoming more common. Referral to ultrasound sonographers and obstetricians who are part of a DSD team is increasingly important here. Second, we pay special attention to healthcare professionals not working within a DSD centre as they are often the first to diagnose or suspect a DSD, but are not regularly exposed to DSDs and may have limited experience. Their thoughtful communication to patients, carers and colleagues, and the accessibility of protocols for first-line management and efficient referral are essential. Careful communication in the prenatal to neonatal period and the adolescent to adult transition are equally important and relatively under-reported in the literature. Third, we discuss the timing of (NGS-based) molecular diagnostics in the initial workup of new patients and in people with a diagnosis made solely on clinical grounds or those who had earlier genetic testing that is not compatible with current state-of-the-art diagnostics.